Boko Haram Insurgency in Nigeria: Religiosity or Alice in Wonder-Land? - Mahmud, Umar Elems; Aliegba, Becky; Oklobia, Omadachi (NIU Journal of Humanities, 2020)
This study attempts a programmed expository analysis of Boko Haram insurgency in Nigeria with major objective to examine the philosophy of the sect and the terrorism. Using content analytical approach, the study examines the modus operandi of the insurgents, in a bid to answer the question as to whether or not Boko Haram is motivated by religiosity, or by the adventure into terrorism, or mutatis-mutandis, by a share desire to spring wonders. Flowing from the analysis of the natural name of the sect, and its mode of operation, the findings of the study reveal that Boko Haram insurgency is primarily against the West and its culture, with no evidence of bias against any religion: Islam, Christianity, Hinduism, Budism, et-cetera. Concluding, the study surmises that Boko Haram insurgency in Nigeria is intended to initiate and propagate intractable terrorist attacks designed to undermine and rubbish the internal security integrity and capability of the Nigerian State, and recommends, modus vivendi, a political dialogue, to complement the ongoing military counter insurgency option. Keywords: Boko Haram, Insurgency, Terrorism, Philosophy, Religiosity, Frustration